Is soleus muscle-tendon-unit behavior related to ground-force application during the sprint start? - Schrödter, E.; Brüggemann, G. P.; Willwacher, S. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To describe the stretch-shortening behavior of ankle plantar-flexing muscle-tendon units (MTUs) during the push-off in a sprint start.